Oral health in the agenda of priorities in public health - José Leopoldo Ferreira Antunes; Tatiana Natasha Toporcov; João Luiz Bastos; Paulo Frazão; Paulo Capel Narvai; Marco Aurélio Peres (Universidade de São Paulo, 2016)
ABSTRACT This study describes the scientific production on oral health diffused in Revista de Saúde Pública, in the 50 years of its publication. A narrative review study was carried out using PubMed, as it is the search database that indexes all issues of the journal. From 1967 to 2015, 162 manuscripts specifically focused on oral health themes were published. This theme was present in all volumes of the journal, with increasing participation over the years. Dental caries was the most studied theme, constantly present in the journal since its first issue. Periodontal disease, fluorosis, malocclusions, and other themes emerged even before the decline of dental caries indicators. Oral health policy is the most recurring theme in the last two decades. Revista de Saúde Pública has been an important vehicle for dissemination, communication, and reflection on oral health, contributing in a relevant way to the technical-scientific interaction between professionals in this field.